On the Efficiency Factors of Positive Law - S. L. Sergevnin (Теоретическая и прикладная юриспруденция)
The article discusses some of the topical theoretical and legal and philosophical and legal problems of lawmaking. According to the author, the efficiency of the application of legislation in the mechanism of legal regulation directly depends on the quality of lawmaking, including its ideological content and scientific elaboration. Based on the works of reputable lawyers of the past and present, the author convincingly proves that the technique of legislative activity determines the effectiveness of the adopted normative legal acts, the totality of which forms a positive law. Guided by the considerations expressed in the article, the author formulates a number of recommendations aimed at improving the legal, technical and substantive aspects of positive law in order to increase the efficiency of legal regulation.